Bovine Arch and Laterality of Cardioembolic Stroke - Al-Ryalat, Nosaiba; Hadidi, Azmy; Younes, Hadeel; Al-suht, Rawan; Shibli, Dana; Tarawneh, Maher Ahmad; Al Hadidi, Akram Kamal; Alabbadi , Ali M.; Ryalat, Soukaina; AlRyalat, Saif Aldeen (Jordan Medical Journal, 2024)
Aims and Objectives: We aimed to find the correlation between cardioembolic and non-cardioembolic stroke incidence with bovine arch anatomical variation. Materials and Methods: Retrospectively, we identified about 1,500 brain MRI/MRA and neck MRA studies, from which 605 patients were found to have had an acute stroke, with a mean age of 62. Images were reviewed to identify anatomical variations of the aortic arch, particularly bovine configuration, and characterization of anterior and posterior circulation stroke. Results: Some 60% of patients had had a left-sided stroke. About 17% of patients had had an anterior embolic ischemic stroke, and another 7% had had a posterior embolic stroke. Within the non-embolic stroke, 56% were in the anterior circulation, while 27% were posterior non-embolic ischemic strokes. Some 30% of the patients were found to have bovine arch; from patients with ischemic stroke and bovine arch, about 17% were in the anterior circulation and 5% in the posterior. Conclusion: The bovine aortic arch is a risk factor for young-onset anterior circulation stroke. Bilateral and left-sided infarcts were more common.